2020
DOI: 10.3928/00220124-20201113-08
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the CRISP Method on the Primary Cardiac Arrhythmia Interpretation Accuracy of Nurses

Abstract: Background: Accurate electrocardiogram (ECG) interpretation is key to quickly providing attention to patients, and the first health staff who evaluate ECGs are nurses. Method: This was a prospective study with a pre–posttest design. The study test included 15 ECGs related to primary cardiac arrhythmias. After pretest nurses were instructed on arrhythmia interpretation using the Cardiac Rhythm Identification for Simple People (CRISP) method, posttests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…One study assessed knowledge of continuous monitoring and intervening with rhythm abnormalities (Chronister, 2014). Educational interventions, including team‐based learning (Kim & Kim, 2020), training in the use of atrial electrograms (McRae et al, 2010), the Cardiac Rhythm Identification for Simple People (CRISP) method (Çıkrıkçı Isık et al, 2020), and the lecture‐discussion approach (VanArsdale, 1998), all led to significant improvement in nurses’ knowledge of ECG interpretation. Cross‐sectional descriptive studies reported varying levels of nurses’ knowledge of ECG interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study assessed knowledge of continuous monitoring and intervening with rhythm abnormalities (Chronister, 2014). Educational interventions, including team‐based learning (Kim & Kim, 2020), training in the use of atrial electrograms (McRae et al, 2010), the Cardiac Rhythm Identification for Simple People (CRISP) method (Çıkrıkçı Isık et al, 2020), and the lecture‐discussion approach (VanArsdale, 1998), all led to significant improvement in nurses’ knowledge of ECG interpretation. Cross‐sectional descriptive studies reported varying levels of nurses’ knowledge of ECG interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…to have low accuracy in ECG interpretation, with recognition rates of fatal ventricular arrhythmias under 30% (Çıkrıkçı Isık et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sehingga dapat disimpulkan metode CRISP dan modified DISBI terbukti sama-sama efektif dalam meningkatkan kemampuan perawat dalam melakukan interpretasi EKG strip (Wibawa, 2019). Sama halnya dengan penelitian yang dilakukan oleh Isık et al, (2020) menyatakan bahwa metode CRISP adalah metode yang efektif, sederhana dan mudah untuk perawat dalam interpretasi EKG terutama EKG yang mengancam jiwa.…”
Section: Pendahuluanunclassified
“…Terdapat perbedaan dengan hasil penelitian yang dilakukan oleh Marlisa & Pratiwi (2019) dengan mayoritas pendidikan responden adalah S1, menyatakan bahwa semakin tinggi tingkat pendidikan seseorang maka akan semakin baik pula tingkat pengetahuannya.Begitu juga hasil penelitian (Isık et al, 2020). Menyatakan bahwa ada perbedaan yang signifikan antara skor pretes perawat yang memiliki pendidikan pascasarjana tentang interpretasi EKG dan yang tidak (p = 0,002).…”
Section: Pembahasan Kemampuan Perawat Dalam Interpretasi Ekg Normal Dan Aritmiaunclassified